Access to Finance for Smallholder Farmers - International Finance Corporation (Washington, DC, 2015)
The percentage of smallholders with access to finance is equally difficult to quantify. According to estimates, even promising approaches to expanding smallholder lending, such as value chain finance, are reaching fewer than 10 percent of smallholders, primarily those in well-established value chains dedicated to higher value cash crops. International Finance Corporation (IFC) has been engaged for several years in learning efforts through diverse partnerships to obtain insights into the challenges of agricultural finance. The evidence of microfinance institution (MFI) involvement in financing commercial and semi-commercial smallholders remains anecdotal and lacks specifics on what makes MFI lending to these segments feasible, and what restricts their reach and effectiveness. This IFC study aims to identify and disseminate lessons emerging from the work of MFIs that have implemented agricultural operations targeting agricultural smallholders in Latin America and the Caribbean (LAC) to support replication and expansion of scalable approaches. Through this research, IFC seeks to understand the motivations of MFIs that venture into agricultural finance, how the products they offer have been structured, and how they were implemented, with a specific focus on agricultural finance programs, and products that are designed for smallholders in loose value chains and non-commercial (subsistence) farmers.